Quantitative Measurement of Job Satisfaction and Antecedents in the Automotive Industry: Review of Instruments in the Last Two Decades - Suwignyo, Suwignyo; Perdhana, Mirwan Surya (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
The study reviews available quantitative instruments that research can use to measure job satisfaction and its antecedents in the automotive industry. Search and collection of literature used in this study using Google Scholar, Emerald Journal, and Elsevier Journal finder using the phrase job satisfaction, the automotive industry and its antecedents for 2010 to 2020. The literature search focuses on the instruments used to measure job satisfaction. In the automotive industry. This study analyzes each job satisfactions instrument used by comparing where the research takes place. The antecedent variables studied were the dimensions of job satisfaction and the number of citations available. The research instruments used are of many variations. Researchers can use the appliance to measure job satisfaction with or without modifying the content in the job satisfaction instrument used. The researcher can choose the right instrument according to environmental conditions, antecedent variables, and the purpose of the research being conducted.